Relationships of urolithogenicity index with some components of urine composition in healthy old female rats - Viktor Flyunt; Igor-Severyn Flyunt; Sofiya Ruzhylo; Oksana Fihura; Dariya Popovych; Xawery Żukow (Kazimierz Wielki University, 2021)
Background. Despite the long history, the results of studies of the impact of balneotherapy in the resort of Truskavets on the lithogenicity of urine are ambiguous, so the topic remains relevant. The aim of this study was to determine the relationship between the lithogenicity index of urine and a number of components of its composition. Materials and Methods. Experiment was performed on 60 healthy old female Wistar rats 220-300 g. Ten animals remained intact, using daily water from drinking ad libitum. Other animals for 6 days were loaded through the tube with daily and various mineral waters at a dose of 1,5 mL/100 g of body mass. The day after the completion of the drinking course collected daily urine, which determined the content of a number of components of the composition. We calculated urine lithogenicity index (Lith) by the formula: Lith = (Uric acid•Calcium/Magnesium•Creatinine)0,25. Results. The most significant effect on the Lith is the concentration of magnesium (r=-0,730), followed by uric acid (r=0,583), calcium (r=0,352) and creatinine (r=-0,298). Medium molecular polypeptides, catalase, sodium, phosphates and urea has been identified as prolithogenic factors while tubular reabsorption of water as litholytic factor. The chemical composition of the fluids consumed by animals has little effect on the lithogenicity index of urine. Conclusion. Both prolithogenic and litholytic factors are present in the urine, which depend little on the chemical composition of the fluid used.